Vochysia tucanorum Mart. butanol fraction presents antitumoral activity in vivo and prevents the installation of cachexia in solid Ehrlich tumor model - Morgan, Henrique Jorge Novaes; Delgado, Aislan Quintiliano [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Camaforte, Nathalia Aparecida De Paula [UNESP]; Dokkedal, Anne Ligia [UNESP]; Bosqueiro, Jose Roberto [UNESP] (Bmc, 2021)
Background Cancer is a multifactorial disease caused by uncontrolled proliferation of cells. About 50-80% of cancer patients develop cachexia, a complex metabolic syndrome associated with an increase of mortality and morbidity. However, there are no effective therapies in medical clinic for cancer cachexia. Vochysia tucanorum Mart. is a common three of the Brazilian Cerrado. The butanolic fraction of V. tucanorum (Fr-BuVt), very rich in triterpenes with various biological activities, might be interesting in being tested in cancer cachexia syndrome. Hence, the present study was undertaken to investigate the antitumoral activity of Fr-BuVt and its potential against cachexia development. Methods Ehrlich tumor was used as model of cancer cachexia. Ascitic Ehrlich tumor cells were collected, processed and inoculated subcutaneously in saline solution (1 x 10(7)/100 mu l; >= 95% viability) for the obtention of solid Ehrlich carcinoma. After inoculation, solid Ehrlich carcinoma-bearing mice were treated by 14 consecutive days by gavage with Fr-BuVt (200 mg/kg). Body weight and tumor volume were measure during the treatment period. Tumors were removed, weighed and properly processed to measure the content and phosphorylation levels of key-proteins involved to apoptotic and proliferation process by Western Blot. Muscles and adipose tissues were removed for weighed. Serum was collected to cytokines levels and energetic blood markers measurements. Results The treatment with the Fr-BuVt (200 mg/kg, 14 days) decreased the solid Ehrlich tumor volume and weight besides increased the expression of the pro-apoptotic proteins caspase-3 and BAX, but also decreased the expression of the proteins involved in proliferation NF kappa B, mTOR and ERK. In addition, our data shows that the administration of Fr-BuVt was able to prevent the installation of cancer cachexia in Ehrlich carcinoma-bearing mice, since prevented the loss of body weight, as well as the loss of muscle and adipose tissue. Moreover, an improvement in some blood parameters such as decrease in cytokines TNF-alpha and IL-6 levels is observed. Conclusions The study revealed that Fr-BuVt has antitumoral activity and prevent installation of cancer cachexia in Ehrlich model. Therefore, Fr-BuVt may represent an alternative treatment for cancer cachexia.
Keywords: Anti-apoptotic; Anti-proliferation; Cancer cachexia; Metabolic syndrome; Triterpenes